Evaluation of the efficiency of dewatering sludge with high inorganic content using a roller press - Vasylenko, Anton (National Technical University "Kharkiv Polytechnic Institute", 2025)
The paper presents the results of an experimental evaluation of the efficiency of a roller press when dewatering sludge with a high content of inorganic substances. Comparative analysis with a decanter centrifuge and a screw press was performed. The research demonstrated the advantages of the roller press in terms of energy efficiency, wear resistance, and dewatering performance, particularly under conditions of high mineral content in the sludge.
Keywords: sludge dewatering; roller press; inorganic content; energy efficiency; wear resistance